Māma ki tama : feeding families in a food insecure environment : a qualitative study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Human Nutrition at Massey University, Albany, New Zealand - Urlich, Joanne Lisa (Massey University, 2021)
Background: More than one in five children in New Zealand live in food poverty, meaning that they live without access to sufficient wholesome food for good health. Evidence suggests that Māori Mothers are more likely to experience food insecurity due to inequities in income, education, employment, and housing security. To achieve and maintain optimal health, a healthy diet is vital. Understanding food security experiences and perspectives which can impact nutrition status is necessary to improve health outcomes and reduce healthcare costs. Kaitaia is a small town located in the Far North of New Zealand that serves a scattered population of around 21,000, where there is a high prevalence of socioeconomic deprivation contributing to poor health outcomes. This study aimed to explore the perspectives and experiences of Māori mothers living in Kaitaia and their strategies to meet food access needs for their whānau (family). Methodology: An inductive approach was undertaken to allow findings to emerge from the data. In-depth unstructured interviews were conducted with twenty Māori mothers living in the Kaitaia region who had at least one child aged two years or younger. Interviews investigated dietary habits and routines, methods of food procurement, nutrition knowledge, skills and perceptions towards healthy food. Demographic characteristics of the participants were collected using a questionnaire. Recorded interviews were transcribed and thematic analysis using NVivo was undertaken to identify, analyse and report themes emerging from the data. Results: Three key themes were identified. Firstly, ensuring the whānau are fed, secondly accessing food from multiple avenues is a time-consuming journey and finally the need to cope with the unexpected and unplanned. Being well-connected to whānau, community groups, support services and having online digital access was pivotal for Māori mothers to meet whānau food needs. Conclusions: Māori mothers placed priority on ensuring that their whānau are fed, with cost and taste of food the driving factors in food purchase decisions. Connections were key to navigate multiple avenues to access food and to cope with unexpected and unplanned circumstances.
Keywords: Māori Masters Thesis; 321005 Public health nutrition; 451004 Te horakai me ngā kai o te Māori (Māori diet and nutrition)